Can You Catch Me: Query Service For Location Preserving - Dr.M.Sree Vani, Dr. Keshetti Sreekala (International Journal of Advanced Science and Technology, 2020)
Area Based Service (ABS) has gotten progressively well-known with the sensational development of advanced mobile phones and informal organization administrations (SNS), and its setting rich functionalities draw in extensive clients. Numerous ABS suppliers utilize clients' area data to offer them comfort and helpful capacities. In any case, the ABS could extraordinarily break individual security since area itself contains a lot of data. Consequently, protecting area security while accomplishing utility from it is as yet a difficult inquiry now. The proposed convention permits various degrees of area question on encoded area data for various clients, and it is productive enough to be applied in work area stages. In cryptography, encryption is the way toward encoding a message or data so that solitary approved gatherings can get it. Encryption doesn't itself forestall impedance, however, denies the comprehensible substance to a future interceptor. In an encryption plot, the proposed data or message, alluded to as plaintext, is scrambled utilizing an encryption calculation creating figure message that can be perused just whenever unscrambled. An encryption plot ordinarily utilizes an arbitrary encryption key created by a calculation. It is hard to unscramble the message without having the key and without utilizing extensive computational assets and abilities. An approved beneficiary can without much of a stretch decode the message with the key. The task Search me on the off chance that you can - Location Query administration targets building up an apparatus for Encryption and Decryption of Latitude and Longitude subtleties utilizing RSA calculation, which is valuable to the divisions like armed force and naval force, where the messages are to be transmitted in a profoundly made sure about way.